Why is Finland lagging behind in export growth? - Sami Oinonen; Matti E. E. Virén (Bank of Finland, 2022)
This paper tries to find an answer to the question of why has Finnish exports performed so poorly during the last two decades. It also tries to assess the related question of why is the level of openness of the Finnish economy much lower than in neighboring countries and countries with similar size and structural features of the economy. The market share analysis shows that Finnish export performance has suffered from unfavorable structure of markets and commodities in particular during the last ten years. The quality of exports has also deteriorated over time so that the share of raw materials and intermediate goods has grown. This has had unfavorable implications on export prices and the terms of trade.
urn:nbn:fi:bof-202206221303
Keywords: F14; F43; F62; 330; export performance; export market share; gravitation model